2001
DOI: 10.1046/j.1537-2995.2001.41020287.x
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the development of RBC substitutes

Abstract: ABBREVIATIONS: AIHA = autoimmune hemolytic anemia; CNS = central nervous system; CO 2 = carbon dioxide; FiO 2 = fractional inspired oxygen; HbOC(s) = hemoglobin-based oxygen carrier(s); LEHb = liposome-encapsulated hemoglobin; NO = nitric oxide; PABD = preoperative autologous blood donation; pO 2 = partial pressure of O 2 ; PHP = pyridoxyl hemoglobin polyoxyethylene; POE-PTCA = percutaneous transluminal coronary angioplasty polyoxyethylene; RES = reticuloendothelial system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
118
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 81 publications
0
118
0
2
Order By: Relevance
“…Hb solutions are potentially clinically useful for resuscitation, elective surgery, shock, cancer therapy, sickle cell anemia, coronary balloon angioplasty, stroke. and myocardial ischemia (8,9). In previous reports, it was found that the interaction of Hb with LPS results in a significant increase of the biological activity of LPS (8, 10 -12).…”
mentioning
confidence: 97%
“…Hb solutions are potentially clinically useful for resuscitation, elective surgery, shock, cancer therapy, sickle cell anemia, coronary balloon angioplasty, stroke. and myocardial ischemia (8,9). In previous reports, it was found that the interaction of Hb with LPS results in a significant increase of the biological activity of LPS (8, 10 -12).…”
mentioning
confidence: 97%
“…Third, it must be retained in plasma for a clinically relevant period of time. Finally, it must be costeffective and convenient in order to achieve widespread use [24].…”
Section: The Rationale For Hemoglobin Substitutesmentioning
confidence: 99%
“…This membrane protects the hemoglobin tetramers; without it, the tetramers would quickly dissociate into dimers and monomers, which subsequently get cleared by the kidney [24]. The average RBC carries its hemoglobin for an average of 120 days before being destroyed [8].…”
Section: The Rationale For Hemoglobin Substitutesmentioning
confidence: 99%
See 1 more Smart Citation
“…10 O desenvolvimento desses produtos tem tido progresso considerável ultimamente. 11,12 zação da Hb para que viesse a ser usada como carreador de oxigênio livre de células. 20,21 Modificações estruturais da Hb incluem: ligação quí-mica cruzada a fim de estabilizar os tetrâmeros de Hb; polimerização da Hb produzindo moléculas de alto peso molecular, encapsulação de vários preparados de Hb e molé-culas de Hb recombinantes por engenharia genética.…”
Section: Introductionunclassified